Janov: městská část Litvínova. Komu se tu hodí vyloučená lokalita? - Barbora Benešová (AntropoWebzin, 2010)
This article is not about any new observation in this locality, but more about the systemization and processing the data already discovered. The main part is based on a survey performed in autumn 2009. The survey comprised of an observation and interviews with officials as well as with local citizens. The main goal of this thesis is to point out the problems of Janov which are intentionally placed aside or just not published. Last but not least, the article is also a reflection of the projects presented up to now and intended for excluded localities, same localities as Janov became in year 2006.